RebkeBeckerColchero_ProceedingsB_All_Data - Rebke, Maren; Becker, Peter H.; Colchero, Fernando (Dryad Digital Repository, 2016)
This folder includes the following files: RebkeBeckerColchero_ProceedingsB_Data.csv - This is the main data file used for the paper. It includes the individual-based data of common terns (Sterna hirundo). RebkeBeckerColchero_ProceedingsB_AddData_Ringed.csv - This is an additional data file used for the paper. It includes a list of partners appearing in the main data file in the column PartnerID, that were marked by ring only and not by transponder. RebkeBeckerColchero_ProceedingsB_AddData_Nests.csv - This is an additional data file used for the paper. It includes a list of the breeding year and the corresponding number of nests in the colony.